Can a great resume hurt? Gender and contrast effects on recruiting - Schleich, Aurélie (2014)
Recruiters make many inferences about applicants' abilities and interpersonal attributes on the basis of applicants' resumes. For example, every once in a while, a good resume leaves a strong positive impression and the recruiter creates a high expectation for the selection interview. What if a disappointing interview follows? Will the great resume help or hurt the candidate? The purpose of this study is to assess the impact of a good resume on the recruiter’s evaluation of a candidate when a non-enthusiastic interview follows as well as the interacting role of gender. The results of two online experiments (n=454) where participants played the role of the recruiter, showed that, on average, a very good resume (vs. no resume) before a non-enthusiastic interview did not affect the recruiter’s evaluation of the candidate. However, when the recruiter’s and the candidate’s gender were taken into consideration, a different picture emerged. While no effect was found for male recruiters, the candidate’s resume had a clear significant impact on female recruiter’s evaluations: when the candidate was also a female, the good resume shown before the non-enthusiastic interview performance tended to help, whereas when the candidate was a male, the good resume had a significant negative effect on female recruiters’ evaluation of the candidate. In sum, in situations where the resume had a strong impact on the recruiter’s evaluation (female recruiters), the direction of the effect was moderated by the candidate’s gender. Gender differences in information processing as well as in-group/out-group biases due to gender matching are used to hypothesize and explain the main findings.